2001
DOI: 10.2134/jeq2001.303998x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Nutrient Source Effects on Surface and Subsurface Water Quality at Corn Planting

Abstract: This study quantified the effects of tillage (moldboard plowing [MP], ridge tillage [RT]) and nutrient source (manure and commercial fertilizer [urea and triple superphosphate]) on sediment, NH4+ -N, NO3- -N, total P, particulate P, and soluble P losses in surface runoff and subsurface tile drainage from a clay loam soil. Treatment effects were evaluated using simulated rainfall immediately after corn (Zea mays L.) planting, the most vulnerable period for soil erosion and water quality degradation. Sediment, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 30 publications
9
90
3
4
Order By: Relevance
“…Indeed, no-till has been shown through many studies to increase SP loading compared to tilled fields (Gaynor and Findlay 1995;Zhao et al 2001; Smith et al 2015a). Practices such as residue management (i.e., no-till and reduced tillage), buffer strips, and cover crops have been suggested to reduce P losses to water.…”
Section: Abstract: Cover Crops-fertilizer Management-phosphorus Stramentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, no-till has been shown through many studies to increase SP loading compared to tilled fields (Gaynor and Findlay 1995;Zhao et al 2001; Smith et al 2015a). Practices such as residue management (i.e., no-till and reduced tillage), buffer strips, and cover crops have been suggested to reduce P losses to water.…”
Section: Abstract: Cover Crops-fertilizer Management-phosphorus Stramentioning
confidence: 99%
“…Great efforts were made to increase adoption of conservation tillage, preferably no-till, to reduce sediment losses to water bodies and thereby induce a concomitant decrease in P loading. Some water quality experts have suggested that increases in SP loading that occurred with simultaneous peak adoption of no-till indicates a causal link between these two events (Smith et al 2015c).Indeed, no-till has been shown through many studies to increase SP loading compared to tilled fields (Gaynor and Findlay 1995;Zhao et al 2001; Smith et al 2015a). Practices such as residue management (i.e., no-till and reduced tillage), buffer strips, and cover crops have been suggested to reduce P losses to water.…”
mentioning
confidence: 99%
“…While there are still some reservations regarding the use of simulated rainfall in place of natural rainfall (Potter et al 2006), there is widespread support for the use of rainfall simulation experiments to obtain some estimate of the magnitude of potential losses from different land management systems, soil types, and landscapes (Pote et al 1999;Bundy et al 2001;Sharpley et al 2001b;Schroeder et al 2004;Tarkalson and Mikkelsen 2004;Little et al 2005). Numerous studies outside Ireland have utilised rainfall simulation to evaluate nutrient losses in runoff from tillage systems (Andraski et al 1985;Zhao et al 2001;Daverede et al 2003;Franklin et al 2007). Studies have also been conducted using laboratory rainfall simulation on f lumes packed with tillage soil to predict the runoff of SS and PP using simple soil tests (Udeigwe and Wang 2007).…”
Section: Phosphorus Mobilisationmentioning
confidence: 99%
“…In a 2-yr study, Lentz and Lehrsch (2010) monitored runoff from fall-applied vs. springapplied manure; however, manure rates between the two applications were dissimilar. Management eff ects on runoff water quality from manure-amended fi elds are well documented for rainfall events (Zhao et al, 2001;Andraski et al, 2003;Little et al, 2005;Smith et al, 2007;Soupir et al, 2006;Gilley et al, 2007;Kaiser et al, 2009). Th e entire soil surface typically interacts with applied water during rainfall and fl ood irrigation events, while during furrow irrigation, only that fraction of the soil surface within the furrows interacts with the applied water.…”
Section: R D Lentz* D T Westermann (Retired)mentioning
confidence: 99%